2. COGNITIVE BEHAVIOUR THERAPY FOR PEOPLE WITH PSYCHOSIS. (9th April 2019) - Morrison, Anthony
Abstract: Cognitive behaviour therapy (CBT) for psychosis is a psychological treatment that is recommended in international guidelines for the treatment of people with psychosis and schizophrenia. However, there is little robust evidence regarding whether psychological therapies can be effective as an alternative to antipsychotic medication, either for those who choose not to take medication or for those for whom antipsychotic medication has been ineffective. Data from several recent randomised controlled trials will be presented to explore these issues. Data from two pilot trials suggest that CBT for people with psychosis may be helpful to those who choose not to take antipsychotics or those willing to be randomised to CBT without medication. A large, definitive randomised controlled trial (n=485) examined whether CBT would be helpful to people who met criteria for treatment resistant schizophrenia who had not shown an adequate response to clozapine. This trial demonstrated that CBT resulted in a significant improvement in overall symptoms at end of treatment (9 months) in comparison to treatment as usual, but that this benefit was not maintained at long-term follow-up (21 months). CBT trials have been criticised for ignoring the possibility of adverse effects; however, there was no data to suggest that CBT caused more adverse effects than treatment as usual. The implications of these findings for clinical practice and for future research will be discussed.